The effect of white and green LED-lights on the catch efficiency of the Barents Sea snow crab (Chionoecetes opilio) pot fishery. - Kristine Cerbule (Public Library of Science (PLoS), 2021)
In commercial snow crab (Chionoecetes opilio) fishery, the catch efficiency of the conical pots is important for increasing the profitability of the industry. This study evaluated the effect of adding green and white light emitting diodes (LED) on the catch efficiency of commercially used conical pots. The results from the field experiments showed that inserting artificial lights significantly increases the catch efficiency for snow crab over the minimum landing size of 95 mm carapace width of up to 76% when using green LED, and by 52-53% on average when using white LED. This study shows that it is possible to improve the catch efficiency of the snow crab fishery by applying artificial LED lights to the conical snow crab pots, potentially resulting in an important economic benefit to the snow crab fishery.